HR ANALYTICS AND BIG DATA AS DIGITAL HUMAN RESOURCE MANAGEMENT TOOLS - KOBETS, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article addresses the topical issue of using HR analytics and Big Data technology in human resource management of modern enterprises. The authors emphasize the importance of digital transformation and optimization of large data processing for effective personnel management in the context of rapid information exchange and the introduction of digital technologies. Despite numerous studies on HR analytics and Big Data in the context of digitalization of the economy, the authors point out the lack of a thorough analysis of the directions, advantages, problems, and prospects of applying these tools in human resource management. The aim of the article is to analyze these aspects of the use of HR analytics and Big Data in personnel management. The article analyzes the literature on this issue, defines the essence and interrelationship of HR analytics and Big Data, and their main areas of application. Based on a generalization of the results obtained, the advantages, problems, and prospects of using HR analytics and Big Data in human resource management are highlighted. The main areas of using Big Data in personnel management are sharing content about vacancies, profiling candidates, communication between recruiters and applicants, analysis of organizational relationships, and development of personnel strategy. HR analytics is used for personnel decision planning, analysis of human resources, career development, recruitment, and personnel evaluation. Key advantages include optimization of managerial decision-making, creation of a favorable communication environment, and consideration of applicants' requests and expectations. Problems of implementation include low motivation of managers, unpreparedness of personnel, and lack of work models. Prospects include the creation of a unified communication environment, the use of universal digital planning and analysis tools, and the implementation of experimental work models. HR analytics and Big Data are effective innovative tools of digital personnel management. Their application allows optimizing the decision-making process, creating a productive communication environment, taking into account the company's requirements and applicants' expectations. Further research should focus on testing these tools in enterprises of various industries and training managers in their effective use.
Keywords: HR analytics; Big Data; optimization of personnel policy; digital transformation; human resource management strategy; digital management tools